A Parental Competence Scale: Dimensions and Their Association With Adolescent Outcomes - Reparaz, Charo; Rivas, Sonia; Osorio, Alfonso; Garcia-Zavala, Gabriela (Frontiers in Psychology, 2021)
Positive family functioning during adolescence is usually studied analyzing parents’ competences and children’s relationship abilities. We present an instrument for the assessment of parental competence, which encompasses both educational style and transmission of values. The objective of the study was to analyze its factor structure and to assess its value in predicting adolescent outcomes. We recruited 2459 high school students, aged 12-15, in 40 schools from Spain, Peru, Mexico, and Chile. They responded to the instrument and to other questions regarding lifestyles. Exploratory and confirmatory factor analyses were carried out in order to assess the internal structure of the instrument, and internal consistency of the resulting dimensions was calculated. Finally, regression analyses were performed to establish associations between the parenting dimensions and adolescent outcomes. Factor analyses showed a consistent structure in the four countries, with good fit indices. The final four factors include parenting styles (affection and control) and education in values (fortitude and privacy). Regression analyses showed associations with adolescent outcomes. For example, adolescents' life satisfaction was best predicted by affection and education in fortitude.